English Language Teaching Textbook in Makassar University - Sahril Nur; Mustakim Mustakim; Muh. Safar Nur; Asia Masita Haidir; Asbar Asbar (Universitas Muhammadiyah Enrekang, 2022)
The aims of this study is to investigate the experiences of 12 Makassar University lecturers lecturers in planning and writing their English language teaching (ELT) textbooks. The results of interpretative phenomenological analysis (IPA) revealed that, despite a number of pedagogical issues and challenges, these lecturers had a positive attitude toward writing their ELT textbooks, as revealed by an in-depth semi-structured individual interview (IDI) and a focus group discussion (FGD). They believed that creating teaching resources for their classes would not only help them meet their students' linguistic demands, but would also improve their lecturing experience. This article argues that writing a textbook for classroom use is a form of pedagogical reflective practice for lecturers that allows them to provide their students with appropriate activities and lessons for effective language teaching and learning, drawing on Tomlinson's notion of the importance of personalizing and localizing ELT textbooks to maximize students' learning. The findings' ramifications are addressed, and recommendations are made.